RANDOMIZED CONTROLLED TRIAL ON CUTTING THE PERIPHERALLY INSERTED CENTRAL CATHETER IN NEONATES - Wosnes, Thaline dos Reis; Giacomozzi, Clélia Mozara; Giacomozzi, Letícia Morgana; Silva, Regina Paula Vieira Cavalcante (Cogitare Enfermagem, 2022)
Objective: To compare the complications between the Peripherally Inserted Central Catheter with length adjustment with cut and without cut. Method: Randomized controlled trial. Composed the sample 46 neonates admitted to a Neonatal Intensive Care Unit service in Paraná, Brazil, between April and July 2021, with catheter indication. Participants were electronically randomized and divided into a control group, whose catheter length was adjusted by cutting it, and an experimental group, whose catheter was kept uncut. Data were analyzed by Mann-Whitney test and Fisher’s test. Results: The mean length of catheter stay was ten days in both groups (p=0.79). No relevant difference was identified regarding complications, such as infiltration, obstruction, and infection. Conclusion: Catheter cutting for length adjustment does not interfere in the complications presented. REBEC Register: RBR-2w4dpg5.